A Study on Remote Sensing and GIS Application for Water Resources Studies - Siddharam. S. Hangaragi, (AG Volumes, 2022)
An important issue in hydrological and water management research is the scarcity of available data, which is particularly true in underdeveloped nations where funding is limited. Remote sensing has shown to be an effective option for water resources management since it delivers geographically and temporally consistent information. For water resources research and management in data-poor locations, this study focuses on remote sensing (RS) and geographic information systems (GIS). RS may be utilized for crop categorization, rainfall and snowfall estimate, soil moisture analysis, surface and groundwater usage, as well as water resources planning and management, when combined with GIS.